A case of attention-deficit/hyperactivity disorder diagnosis: Sir Karl and Francis B. slug it out on the consulting room floor - McHoul, Alec and Rapley, Mark (Discourse & Society, 2005)
Drawing upon Conversation Analysis and Critical Discourse Analysis, and in the frame of what is currently called discursive psychology, we open up a significant macro-social problem - indeed a global problem - to inspection at a local level by reference to a naturally-occurring instance of talk-in-interaction. The problem is the documented increase in diagnoses of attention-deficit/hyperactivity disorder (ADHD) in recent years - particularly for boys, particularly in Anglophone countries, and particularly by reference to school-based conduct - and its consequent ‘treatment’ by amphetamines (including Ritalin [methylphenidate]) and related medications (Singh, 2002a). The local instance of talk-in-interaction is a transcript of a diagnostic session involving a young boy, his parents and a paediatrician. We aim to show that the local instance can shed light on just how routine and mundane it is for children to be positively diagnosed and medicated merely on presentation for the possibility of the ‘disorder’, even when parents are manifestly sceptical about (even resistive to) the diagnosis and its methodological grounds.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTA1MDUxMTcz